Pengaruh Rektrukturisasi Kredit di Masa Pandemi Covid-19 Terhadap Pendapatan pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Muhammad Reza Septriawan; Sri Mulyani; M Iqbal (Ekonomis: Journal of Economics and Business, 2021)
The research will look at the impact of credit restructuring on the income of banks in Indonesia. This research was conducted with a quantitative approach, with reference to the data used is secondary data, in the form of financial reports of all banking issuers (45 issuers) which are reported and summarized on the official website of the Indonesia Stock Exchange (BEI). The results of hypothesis testing using the t test show a significance value of 0.00 <0.05 with a coefficient value of -1.260, which means that credit restructuring has a negative effect on bank income, it can be concluded that the credit restructuring variable (X) partially has a negative effect on the income variable. (Y). The higher the credit restructuring, the lower the income of banking companies listed on the IDX. The result of the coefficient of determination shows the ability of the independent variable to explain the variation of the dependent variable of 0.945 or 94.5%, which means that the effect of credit restructuring (X) on income (Y) is 94.5% and the remaining 5.5% is influenced by other variables outside of this research model.